Non-Resident Deposits in India: A conceptual study - Dr. Neelam Sethi (Innovative Research Thoughts, 2023)
Non-Resident Deposits are an important source of foreign currency since they are unconditional and hence a confirmed and reliable supply of foreign currencies. FCNR Deposit Accounts (Foreign Currency Non-Resident Account) are a significant part of non-resident deposits since they are not affected by currency changes. Unique to India, a Foreign Currency Non-Resident (FCNR) Deposit is designed for non-resident “Indians (NRIs) and people of Indian origin (PIOs) to save funds in their preferred foreign currency. Most often used currencies are the US dollar, British pound, Euro, Japanese yen, Australian dollar, and Canadian dollar. An FCNR deposit's main benefit is that the depositor may choose any period from 1 to 5 years without worrying about currency conversion rates. This kind of deposit is crucial to the development of a courtier's financial standing. In order to raise interest in expanding these deposits among NRIs, the researchers have investigated this issue in depth with regard to its idea and significance.